Il complesso monumentale di Baitokaike (Hoson Sulaiman - Siria) - Ahmad, Tarek, (Archaeopress Roman archaeology ;, 2018)
The architecture of the temple at Baitokaike shares the characteristics that are typical of the Phoenician region, especially during the imperial era. This study aims to deepen our knowledge, proposing new chronological phases of the site, starting from the time when it was an open cult place, through the architectural analysis of its buildings.